2010
DOI: 10.1111/j.1742-1241.2010.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of almotriptan in early intervention for treatment of acute migraine in a primary care setting: the START*study

Abstract: Summary Aims:  The benefits of taking almotriptan early for acute migraine when pain is mild have clearly been demonstrated in the neurology setting. The aim of this study was to determine whether similar benefits with early intervention of almotriptan can be achieved in everyday general practice, where most migraineurs are managed. Methods:  In this European, prospective, observational study, patients were asked to treat up to three migraine attacks over a 2‐month period with almotriptan 12.5 mg administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…[11][12][13][14][15] Adverse event rates are similar to placebo 13,16 and there was no significant difference in overall adverse event rates reported in those who treated the migraine headache early compared to late. 12,15 Only two of the four early treatment studies reported premature discontinuation rates. 12,13 (See Table 1) The first was a head to head comparison of early to standard treatment with almotriptan.…”
Section: Safetymentioning
confidence: 74%
See 1 more Smart Citation
“…[11][12][13][14][15] Adverse event rates are similar to placebo 13,16 and there was no significant difference in overall adverse event rates reported in those who treated the migraine headache early compared to late. 12,15 Only two of the four early treatment studies reported premature discontinuation rates. 12,13 (See Table 1) The first was a head to head comparison of early to standard treatment with almotriptan.…”
Section: Safetymentioning
confidence: 74%
“…15 Patients were 18 to 65 years of age and had migraines with or without aura of at least moderate intensity for at least 1 year. They had to have 2 to 6 migraines per month for the last three months to be included in the trial.…”
Section: Efficacymentioning
confidence: 99%
“…Almotriptan 12.5 mg was found effective for their treatment, producing a 48.4% 2-h-pain-free rate and 2-24-h-sustained pain-free in most patients [19]. In the START study [20], 1174 migraine attacks were treated with almotriptan 12.5 mg within 1 h of pain onset and when pain was mild.…”
Section: Triptansmentioning
confidence: 98%
“…Triptane können zu jedem Zeitpunkt innerhalb der Attacke wirken, das heißt, sie müssen nicht notwendigerweise unmittelbar zu Beginn der Schmerzphase eingenommen werden. Triptane wirken umso besser, je früher sie in einer Migräneattacke eingenommen werden (73)(74)(75)(76)(77)(78). Um der Entwicklung eines Kopfschmerzes durch Medikamentenübergebrauch vorzubeugen, sollte eine frühe Einnahme nur empfohlen werden, wenn die Attacken nicht zu häufig sind (< 10 Kopfschmerztage pro Monat) und wenn der Patient eindeutig seinen Kopfschmerz als Migräneattacke identifizieren kann.…”
Section: Empfehlungunclassified